Insertion Des Jeunes À Risque À Travers Les Opportunités D’activités Économiques Offertes Dans Le Secteur Des Transports En Commun À Abidjan - Hermann, Crizoa (European Scientific Journal, ESJ, 2018)
The study aims to show that the public transport sector in Abidjan, constitutes a pool of jobs likely to allow the social integration of young people at risk of committing crimes and offenses. To achieve this goal, 207 people were interviewed empirically from a judgment sample through municipalities in the city of Abidjan. The data collected were analysed and processed qualitatively and quantitatively. The results of the survey reveal that the Abidjan public transport environment, essentially perceived as a niche for the development of urban insecurity, enables the social integration of many young people at risk by the opportunities for economic activities that are available to them without qualification.